Programmed cell death protein-1 (PD-1) inhibitor therapy in patients with advanced melanoma and preexisting autoimmunity or pilimumab-triggered autoimmunity - Gutzmer, Ralf; Koop, Anika; Meier, Friedegund; Hassel, Jessica C. (European journal of cancer, 2017)
Programmed cell death protein 1 (PD-1) inhibitors are a common treatment strategy for metastatic melanoma and other tumour entities. Clinical trials u…